2020
DOI: 10.1186/s12888-020-02808-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and remission of depressive symptoms and psycho-social correlates in Chinese early adolescents

Abstract: Background: This study aimed to investigate a one-year course of persistent/remitted depressive symptoms and associated demographic and psychosocial factors that predict persistent/remitted depressive symptoms in Chinese high school students. Methods: One thousand five hundred forty-four Grade 7 students provided data for the first wave. Of the initially recruited students, 483 who were classified as depressed (CESD score ≥ 16) at baseline were then tracked and invited to fill in the questionnaire for a second… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Participants who score less than 50 points are considered not to be addicted to the Internet, and those who score more than 50 points are considered to be addicted to the Internet ( Young, 1998 ; Cao et al, 2011 ; Tan et al, 2016 ; Xu et al, 2020 ). We used the Chinese version for evaluation, which had good reliability and validity (Cronbach’s α coefficient = 0.93) ( Lin et al, 2009 ; Cao et al, 2011 ; Tan et al, 2016 ; Chi et al, 2020a ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants who score less than 50 points are considered not to be addicted to the Internet, and those who score more than 50 points are considered to be addicted to the Internet ( Young, 1998 ; Cao et al, 2011 ; Tan et al, 2016 ; Xu et al, 2020 ). We used the Chinese version for evaluation, which had good reliability and validity (Cronbach’s α coefficient = 0.93) ( Lin et al, 2009 ; Cao et al, 2011 ; Tan et al, 2016 ; Chi et al, 2020a ).…”
Section: Methodsmentioning
confidence: 99%
“…Both higher education and high school level education were found to impact sleep. This can be attributable to the fact the educated individuals or students may have academic and professional stressors that may have impacted their mental health and sleep conditions [71][72][73] . Furthermore, social support was found to have a critical role in sleep status and associated disorders.…”
Section: Interventions For Sleep Disordersmentioning
confidence: 99%
“…Recent studies have similarly shown that COVID-19 has affected mental health outcomes such as anxiety, depression, and post-traumatic stress symptoms [6,7,9]. Studies conducted in China in the early phase of COVID-19 found that the pandemic-affected individuals had a wide range of adverse psychological impacts of COVID-19 [21,22,23,24,25]. A recent meta-analysis by Salari et al, reported that the prevalence of stress 29.6%, the prevalence of anxiety 31.9%, and the prevalence of depression 33.7% globally [6].…”
Section: Introductionmentioning
confidence: 99%